Analysis of Push Pull Mooring Factors on Switching Intention in the Use of QRIS among MSMEs in Bantul Regency - Sa'baniyah, Firda; Ratnasari, Asti; Heksaputra, Dadang; Rochmadi, Tri (Sistemasi: Jurnal Sistem Informasi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy, contributing significantly by absorbing 96.92% of the workforce. MSMEs must adapt to technological advancements, particularly in digital payment systems. The Quick Response Code (QR Code) has been introduced as a payment innovation in Indonesia, with the implementation of the Quick Response Code Indonesian Standard (QRIS) mandated by Bank Indonesia for all payment system providers starting January 1, 2020, under PADG No. 24/1/PADG/2022. Data from ASPI shows a 62.95% increase in QRIS adoption by merchants in 2022 compared to the end of 2021. The Special Region of Yogyakarta, particularly Bantul Regency, contributes significantly to the region's GDP, accounting for 15.18%. It is crucial to encourage MSMEs in Yogyakarta to embrace economic digitalization through the use of QRIS in sales transactions. This study analyzes the push-pull-mooring (PPM) factors that influence MSMEs' switching intentions to adopt QRIS. Push factors refer to negative aspects of the old service, pull factors represent positive attributes of the new service, and mooring factors are barriers to switching intention. The research employs the PPM framework and analyzes data using the SEM-PLS method through SmartPLS 4.1. The sample consists of 100 respondents who meet the criteria of MSMEs that have never used QRIS and do not keep sales transaction records in their business. The results indicate that three hypotheses show significant influence, while four are not significant. The latent variables that significantly affect switching intention are saving time, perceived lack of transaction records, and perceived trouble. The analysis reveals that pull factors have a relatively higher impact on switching intention compared to push factors. Mooring factors, represented by the latent variable of habit, show no significant effect on switching intention.